Geochemical Profiling Of A Sulfide Leaching Operation: A Case Study - A. Guzman; R. E. Scheffel; S. M. Flaherty (Society for Mining, Metallurgy & Exploration, 2006)
Geochemical conditions within a leaching operation are heterogeneous. This variability arises mainly from hydrological controls imparted by physical characteristics of the ore and by heterogeneous metallurgical properties at the rock-fragment and industrial heap scale. The resulting chemical conditions are responsible for stratified mineral recovery, non-uniform extraction and prolonged leach cycles. This paper presents field data from a sulfide-leaching operation which clearly demonstrate the impact of chemical heterogeneity on metal recovery and the potential use of modern measuring techniques to facilitate operational monitoring and decision making for optimization of leaching operations.